2019
DOI: 10.1088/1742-6596/1281/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Development of calcium phosphate coatings with regulated porous structure as drug carrier systems

Abstract: The calcium phosphate coatings were formed by the micro-arc oxidation method under different applied voltage. It was shown that the thickness, surface roughness, porosity and sizes of the structural elements of the coatings increased with increasing of the applied voltage. In addition, the increase in the voltage led to the structural-phase transformation in the coatings from the amorphous state to the amorphous-crystalline state with incorporation of CaHPO4, α-Ca2P2O7, β-Ca2P2O7 and TiO2 (anatase) nano-sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The unipolar anodic potentiostatic regime at a fixed pulse frequency of 50 Hz, pulse duration of 100 µs, time of 10 min, and varied voltage from 150 to 300 V with a step of 50 V was used as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The unipolar anodic potentiostatic regime at a fixed pulse frequency of 50 Hz, pulse duration of 100 µs, time of 10 min, and varied voltage from 150 to 300 V with a step of 50 V was used as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the surface morphology and developed relief play a significant role in the interaction of CaP coatings with biological fluids and living systems (cells, bacteria) [37] and when they are used as carriers of drugs. In this case, the porous structure of the coatings plays a special role, since the nature of the porosity, the size, and the pore shape have a significant effect on the processes of drug adsorption and its controlled release [38]. Based on the obtained data, the calibration graph of the dependence of optical density on the number of living cells in the cell suspension (Figure 2b) was plotted.…”
Section: Formation Of the Cap сOatings And Their Structure Morphology...mentioning
confidence: 99%
“…It is known that the surface morphology and developed relief play a significant role in the interaction of CaP coatings with biological fluids and living systems (cells, bacteria) [37] and when they are used as carriers of drugs. In this case, the porous structure of the coatings plays a special role, since the nature of the porosity, the size, and the pore shape have a significant effect on the processes of drug adsorption and its controlled release [38]. The SEM studies demonstrated that CaP coatings with different surface morphologies were formed depending on the applied voltage (Figure 4a-c An increase in the applied voltage from 250 to 300 V led to an increase in the intensity of microarc discharges acting on the substrate; as a result, the surface morphology of the coatings changed.…”
Section: Formation Of the Cap Coatings And Their Structure Morphology...mentioning
confidence: 99%
“…Разработаны и изучены объемные макропористые кальций-фосфатные (КФ) покрытия на титановых матрицах в качестве носителей лекарственных средств, в частности, противоопухолевых препаратов [1]. Синтез КФ покрытий на образцы из технически чистого титана марки ВТ1-0 проводили методом микродугового оксидирования (МДО) при варьировании величины приложенного импульсного напряжения в интервале 150 -350 В. Остальные электрофизические параметры МДО были фиксированными: длительность импульсов тока -100 мкс; частота импульсов тока -50 Гц; форма импульсовпрямоугольная; коэффициент заполнения -0,5 %; длительность процесса МДО -10 мин.…”
Section: институт физики прочности и материаловедения со ран томскunclassified
“…Верхний (поверхностный) КФ слой представлен сфероидальными структурными элементами (сферы, полусферы), имеющими размеры 4-50 мкм, в которых содержатся внутренние поры с размерами 1-20 мкм, также на поверхности присутствуют поры, находящиеся в «нишах» между сфероидальными образованиями. Как показали предыдущие исследования [1,2], основной и поверхностный слои покрытия находятся преимущественно в аморфнонанокристаллическом состоянии, состоящие из аморфного КФ, а также нанокристаллических фаз CaHPO 4 и β-Ca 2 P 2 O 7 .…”
Section: институт физики прочности и материаловедения со ран томскunclassified